Statistics from space: Next-generation agricultural production information for enhanced monitoring of food security in Mozambique - International Food Policy Research Institute (2023)
Centro de Estudos de Políticas e Programas Agroalimentares (CEPPAG). 2023. Statistics from Space: Next-Generation Agricultural Production Information for Enhanced Monitoring of Food Security in Mozambique. Component 3. Digital collection of groundtruthing data. PowerPoint presentation given during the Project Inception Workshop, VIP Grand Hotel, Maputo, Mozambique, April 20, 2023